Discovery of quorum quenchers targeting the membrane-embedded sensor domain of the Staphylococcus aureus receptor histidine kinase, AgrC. Issue 76 (21st August 2020) - Xie, Qian; Wiedmann, Mareike M.; Zhao, Aishan; Pagan, Ivelisse R.; Novick, Richard P.; Suga, Hiroaki; Muir, Tom W.
Abstract : By integrating lipid nanodisc and the RaPID technologies, we identified novel peptidic quorum quenchers targeting S. aureus histidine kinase AgrC. Abstract : We combined mRNA display technology with lipid-nanodisc based selections and identified high-affinity ligands targeting the integral membrane sensor domain of the histidine kinase AgrC as potent inhibitors of Staphylococcus aureus quorum sensing-modulated virulence. Our study highlights the potential of this integrated approach for identifying functional modulators of integral membrane proteins.